Guidelines for the Responsible Use of Deception in Simulation: Ethical and Educational Considerations. Issue 4 (August 2020) - Calhoun, Aaron W.; Pian-Smith, May; Shah, Anjan; Levine, Adam; Gaba, David; DeMaria, Samuel; Goldberg, Andrew; Meyer, Elaine C.
Abstract : Summary Statement: Many techniques and modifications commonly used by the simulation community have been identified as deceptive. Deception is an important issue addressed by both the newly adopted Healthcare Simulationist Code of Ethics and the American Psychological Association Code of Conduct. Some view these approaches as essential whereas others question their necessity as well as their untoward psychological effects. In an attempt to offer guidance to simulation-based healthcare educators, we explore educational practices commonly identified as deceptive along with their potential benefits and detriments. We then address important decision points and high-risk situations that should be avoided to uphold ethical boundaries and psychological safety among learners. These are subsequently analyzed in light of the Code of Ethics and used to formulate guidelines for educators that are intended to ensure that deception, when necessary, is implemented in as psychologically safe a manner as possible.